Współczesny bikameralizm – czyli kształt i sens istnienia dwuizbowego modelu parlamentu - Modzelewski, Bartosz (2019)
Functioning of the bicameral model of a parliament is, at this time, a hot topic of many debates and discussions. The sense of its existence is continuously being challenged, and there is a number of questions being asked about the democracy aspect of this solution. Could it be that an appropriate form and adequate procedures will contribute to an increase of its functionality? May the bicameralism be used for the more profound realisation of new assignments on an empirical and normative level? Pointing at its origins and showing examples of currently operating parliaments in Poland and Great Britain, the author of this article do his best to answer all the above questions and perhaps more – continuously arising ones
Keywords: bikameralizm; parlamenty; prawo konstytucyjne